Forensic ballistics - Manlusoc, Ariel C. (Wiseman's Book Trading, Inc., 2016)
"This book is designed to provide the students the necessary instructional materials that would help them learn and understand the basic principles involved in the identification of firearms. .This work presents a detailed discussion of the four branches of the study of Ballistics, from the time the cartridge was loaded in the firearm as the bullets leaves the gun, while in its flight, after it hits the target up to the identification of the firearms from which it was fired."--Preface